Safety and danger: Perceptions of the implementation of harm reduction programs in two communities in Nova Scotia, Canada. (31st May 2021) - Jackson, Lois A.; Dechman, Margaret; Mathias, Holly; Gahagan, Jacqueline; Morrison, Kirk
Abstract: People who use substances (PWUS), and specifically individuals who use injection drugs and/or smoke crack cocaine, experience risks which harm reduction programmes can help reduce. Prior to implementing harm reduction programmes, however, it is critical to understand how programme users and others in the community perceive the programmes as their perceptions may influence implementation. A mixed‐methods study asked PWUS and key informants about their perceptions of implementing five harm reduction programmes in their communities, including perceptions of the advantages of the programmes, where best to locate them, and community support. Questionnaires were administered to 160 PWUS, and qualitative interviews were conducted with 11 purposefully sampled key informants. Data were collected in one medium‐size and one small‐size community/municipality in Nova Scotia, Canada, during 2017–2018. SPSS was used to generate descriptive statistics and means from the quantitative data, and the qualitative data were analysed for key themes using thematic analysis. Both PWUS and key informants perceived numerous advantages of the harm reduction programmes, but some key informants suggested that there might be potential opposition to the implementation of additional needle distribution and disposal programmes in some locations and potential opposition to safer consumption sites. Further research is needed to understand why these programmes were viewed as potentially generating opposition, but findings suggest that a key factor is the association of the programmes with 'danger' because the programmes are directly linked with criminalized drug use. In contrast, the three other programmes are linked to 'safety' because naloxone saves lives, peer navigation programmes support access to existing programmes and detoxification programmes are associated with safety through the reduction/elimination of drug use. Legalization/decriminalization of drugs might help to change the association of some programmes with 'danger' and therefore help support the implementation of harm reduction programmes that appear to be perceived by some as linked to danger.